DHYAAN: reimagining Tolstoy Farm through a spiritual identity - Ganda, Rachna (My University, 2020)
More than 100 years ago, Mohandas K. Gandhi, an Indian lawyer, politician, social activist, and writer and his friend Hermann Kallenbach, a German born architect shaped the idea of an utopian environment separated from the city. Tolstoy Farm, was founded and located just outside of Lenasia, Johannesburg, which is now owned by Corobrik, where they have declared a portion of the land a heritage site. This thesis explores opportunities for connecting architectural design to the principles and concepts, which emerged out of the narrative and events that took place on Tolstoy farm. South Africans experienced segregation through religion and race. Architecture can be seen as a medium to establish a dialogue among these groups. This design aims to allow its users to experience a new “sense of place” that arouses curiosity, creativity, spirituality and comfort, starting to delve deeper and find the balance between architecture and the human body. This proposal will also explore different methodologies around spirituality to assist the reader in understanding the relationship around principles in Indian culture such as meditation, ayurvedic practices (the human body) and Vaastu Shastra (architecture). It is believed that not only do these elements give us the ability to heal but also boosts the energy around us and uplifts our spirits. This intervention aims to merge seemingly unrelated ideas in an unconventional and unprecedented way, ultimately resulting in a fusion of concepts, highlighting the past and bringing it out into the present. This ‘hybrid’ architectural piece draws on a program, from a healing center, combining a general clinic and an ayurvedic treatment center, which allows harmonious living in an urban landscape. Not only am I looking at the well-being of the users but also architecture that encompasses the teachings around Gandhi on site and the “Satyagraha” movement for non-violent protest. Each part of the program is seemingly different, yet each of them feed off of the other. This enables a multi-sensory ambience, a spatial experience and embodied spirit that resonate within the human soul
A research report proposal submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Masters of Architecture (Professional), 2020
Keywords: Architectural design; Design; Space (Architecture)